2017
DOI: 10.1039/c7ra06460h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epoxy resin on ground-granulated blast furnace slag stabilized marine sediments

Abstract: In this study, an environmentally friendly epoxy resin is mixed with ground-granulated blast furnace slag (GGBS) for use as a stabilizer to enhance mechanical performance and leaching resistance properties of marine sediments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Recall that the organic deposition after stearic acid modification is indicated by the appearance of CO 2 as shown in Table 1. The CO 2 appearance as an indication on organic content has been claimed by other investigations, for example, the reactivity of clay minerals with acids and alkalis and the effect of epoxy resin on ground granulated blast furnace slag composites, consequently .…”
Section: Resultssupporting
confidence: 57%
“…Recall that the organic deposition after stearic acid modification is indicated by the appearance of CO 2 as shown in Table 1. The CO 2 appearance as an indication on organic content has been claimed by other investigations, for example, the reactivity of clay minerals with acids and alkalis and the effect of epoxy resin on ground granulated blast furnace slag composites, consequently .…”
Section: Resultssupporting
confidence: 57%
“…These leaching values are always lower than those of raw sediments shown in Table 3. This problem was previously solved in the study of Du et al (2017), who used the high-grade slags to stabilize sediment-based polymer matrices. Compared with the European Directive (JOCE, 2008), these formulations at different substitution ranges are lower than the threshold of non-dangerous wastes.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the mechanical resistance and durability of these products, recent works have investigated the use of novel binders for replacing the hydraulic ones. Only a few studies that dealt with the use of sediments in polymer matrices (Du et al, 2017; Ennahal et al, 2019) focused on the effects of epoxy resin on marine sediments. These works have shown that the mechanical performance is related to the resin percentages added to the mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Almost all GGBFS is used as a partial substitute for Portland cement in concrete mixes or blended cement. 8,9 Pelletized slag is generally used for lightweight aggregates but can be ground into a material similar to GGBFS. Foamed slag is used as a lightweight aggregate for Portland cement concrete, but its production is less common and is being replaced by the pelletizing procedure.…”
Section: Introductionmentioning
confidence: 99%